IMPLEMENTASI PENDIDIKAN INKLUSIF DI SEKOLAH DASAR: TANTANGAN DAN SOLUSI - Murtadha, Murtadha; Fauzan, Fauzan (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2025)
This study examines the implementation of inclusive education in elementary schools, focusing on the challenges and solutions implemented. Using a qualitative approach with a case study design, the study was conducted in five elementary schools that provide inclusive education. Data were collected through in-depth interviews and participant observations, involving principals, teachers, and students. The results of the study indicate that although the policy supports inclusive education, its implementation still faces various challenges. The main challenges include teachers' lack of understanding of the needs of students with special needs, limited resources, and social stigma. However, innovative practices were also found to overcome these challenges, such as comprehensive teacher training programs, curriculum adaptation, and collaboration between schools, parents, and the community. The study reveals the gap between policy and practice, the importance of teacher capacity development, and the crucial role of school culture transformation in supporting effective implementation of inclusive education. These findings highlight the need for a comprehensive and systemic approach to developing inclusive education, with a focus on capacity development, culture transformation, and collaboration between stakeholders. Implications of the study include the need for policy clarity, greater resource allocation, and community awareness programs to support inclusive education.